DIGITAL TRANSFORMATION AND AI READINESS IN HIGHER EDUCATION: A CASE STUDY IN PUBLIC SECTOR UNIVERSITIES (Contemporary Journal of Social Science Review, 2025)
It looks at the increase in digitization in schools and explores the new options this may bring.  Digital technology allows educational institutions to reach various new possibilities as environments adapt.  The research looks at the current use of technology in schools to highlight the improved possibilities created by its integration.  Several things are contributing to big shifts in higher education such as higher operational costs, the adoption of micro and Nano degrees, the rise of online education, an increase in digitally-literate students and digital transformation everywhere.  Digital tools are being used more often by students to show their knowledge in structured college or university classes.  It looks closely at the role of digital transformation in higher education and examines what benefits it might bring in the future.  Topics such as digital transformation, virtual reality (VR), artificial intelligence (AI) and Technology, Entertainment, Design (TED) courses are reviewed for their importance in shaping the future of education.  It is clear from research that digitalization is only the first part of a bigger process where institutions do not stop at repeating old tasks, but also transform education. According to the study, using new management methods in business can make the most of information and communication technology (ICT).  Educational institutions need to dramatically change their approach and start using innovative methods for teaching, learning and administration when undergoing digital transformation. In the process of changing, institutions give more value to students and develop meaningful partnerships with other organizations in the field.